Трансформація системи платежів за користування землями сільськогосподарського призначення - Хомюк, Наталія Леонідівна; Khomiuk, Nataliia L. (My University, 2016)
Розкрито теоретико-методичні основи дослідження системи платежів за користування землями сільськогосподарського призначення. Здійснено діагностику платності сільськогосподарського землекористування в Україні. Визначено напрями трансформації системи платежів за користування землями сільськогосподарського призначення.

The thesis for the degree of candidate of economic sciences, specialty 08.00.06 – Economics of Natural Resources and Environment. – National University of Water Management and Nature Resources Use, Rivne, 2016. The essence of agricultural land is determined in the dissertation. The classification of the payment system for the use of agricultural land is improved. The retrospective analysis of the genesis of land payments in Ukraine is conducted. The modern trends of agricultural land use in Ukraine are researched. Also, the implementation of land payments is analyzed. The agricultural land use and its serviceability in the region are characterized. The conceptual foundations of transformation in payment for the use of agricultural land are disclosed. The proposals for the improvement of method of normative monetary value of agricultural land are developed. Methodical approaches to formation of the payment system for the use of agricultural land are elucidated, taking into account international experience.
The transformation of payment system for use of agricultural land
Keywords: транформація; сиситема платежів за користування землями сільськогосподарського призначення; плата за землю; єдиний податок для сільськогосподарських товаровиробників; payments for use of agricultural land; transformation of payment system for use of agricultural land; land tax; rent; single tax for agricultural producers